The influence of multi-frame leadership style on organizational climate in a private university in Malaysia: A case study / Mabel Tan Hwee Joo - Mabel, Tan Hwee Joo (2014)

(untitled)
This research examined the leadership style of the vice chancellor of a private university in Malaysia. There is pressure to improve efficiency and effectiveness as private universities experience increasing financial pressures from intense competition amongst institutions. The primary purpose of this case study is to examine the impact of multi-frame leadership style using Bolman and Deal‘s (2008) four-frame model on organizational effectiveness. Leaders are perceived to be effective if they practice multi-frame (three or more frames) leadership style. In this study, the independent variable is Bolman and Deal‘s four leadership frames, i.e. structural, human resource, political and symbolic. The dependent variable is the organizational climate of the university with four domains, i.e. consideration, intimacy, disengagement and production emphasis. The moderating (demographic) variables are gender, age, academic qualification, current position, number of years in current job and managerial experience. This study employed a mixed-method, where quantitative data was collected using Bolman and Deal‘s (1990) Leadership Orientation Survey (LOS) and Borrevik‘s (1972) Organization Climate Description Questionnaire for Higher Education (OCDQ-HE). A pilot study was conducted on one of the deans with 35 participants of the same private university giving a response rate of 94%. Internal consistency reliability coefficients for the constructs of the two instruments were in the range of .69 and .91. The main subject in this study is the vice chancellor with a strong corporate background, an impressive academic resume and a strong global presence. Fifty of the vice chancellor‘s direct reports participated in this study with a response rate of 88%. Descriptive iv statistics such as mean, standard deviation and frequency were used to identify the frames used by the vice chancellor. One sample t-test was conducted to examine leadership effectiveness of the vice chancellor. Inferential statistics such as two independent sample t-test, analysis of variance tests, Pearson correlation tests, and regression analyses were used to examine the relationship between the variables. Results showed that the vice chancellor exhibited leadership style with two frames (structural and symbolic). Multiple regression analyses showed that the human resource frame is a significant predictor for the consideration domain, while the symbolic frame is a significant predictor for the intimacy and production emphasis domains. Demographic variables did not cause any significant differences in outcomes of the study. The qualitative data was collected using interviews, analysis of documents and observations, and data was transcribed and analyzed using the Atlas.ti software. A matrix was compiled with the four leadership frames as thematic codes; and content analysis was carried out. Qualitative results showed that the vice chancellor exhibited three frames (structural, human resource and symbolic), indicating multi-frame leadership. The qualitative data supports the quantitative data as the interviews with the vice chancellor‘s direct reports showed that the vice chancellor also exhibited the human resource frame. Findings from this study can be used to tailor individual development plans focused on leadership frames. Multi-frame leadership may be necessary criteria for appointment of future vice chancellors in universities, complementing the Government‘s plan for universities in meeting the country‘s development needs.